2013
DOI: 10.1007/s11747-013-0363-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the value of commonly used methods for measuring customer value: a multi-setting empirical study

Abstract: Despite the importance of customer value, considerable divergence of opinion exists on how to adequately conceptualize and measure this construct. In this study, four commonly used methods for measuring customer value (i.e., the methods proposed by Dodds et al. (1991), Gale (1994), Holbrook (1999) and Woodruff and Gardial (1996)) are compared. First and foremost, the psychometric properties of the different methods are evaluated. Next, the authors compare the predictive ability of the different methods with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
198
0
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(226 citation statements)
references
References 80 publications
(136 reference statements)
7
198
0
12
Order By: Relevance
“…By the same token, measuring the value delivered to a consumer in many services industries requires apprehending the nature of the service delivered. For example, various CVP measurement methods have been developed to capture CVP in healthcare [Chahal, Kumari, 2012], tourism [Gallarza, Saura, 2006] and service transactions in general [Lin et al, 2005;Ruiz et al, 2008;Huber et al, 2007].…”
Section: Measuring Cvp Why Quantitative Methods Prevail?mentioning
confidence: 99%
See 3 more Smart Citations
“…By the same token, measuring the value delivered to a consumer in many services industries requires apprehending the nature of the service delivered. For example, various CVP measurement methods have been developed to capture CVP in healthcare [Chahal, Kumari, 2012], tourism [Gallarza, Saura, 2006] and service transactions in general [Lin et al, 2005;Ruiz et al, 2008;Huber et al, 2007].…”
Section: Measuring Cvp Why Quantitative Methods Prevail?mentioning
confidence: 99%
“…In reflective models indicators can equal manifestations, and therefore effects of the construct measured, while in formative models indicators are the causes/grounds of the construct formation. Using different models to test the same construct generates different outcomes [Lin et al, 2005]. Authors clearly prove, how divergent managerial implications can be driven while using the conceptual model without knowing its nature and consequences.…”
Section: Conceptual Model and Its' Measurement Consequencesmentioning
confidence: 95%
See 2 more Smart Citations
“…The authors state that loyalty considered as a consequence of value and satisfaction is a widespread reality (Cronin et al, 2000;Gallarza et al, 2011;Leroi-Werelds et al, 2014;Parasuraman and Grewal, 2000;cited in Gallarza et al, 2016). In 2015, Gallarza et al found that satisfaction is the behavioral consequence of perceived value, with loyalty being the final outcome (p. 147).…”
Section: Experience Value-satisfaction-loyaltymentioning
confidence: 99%